Tools for the strategic management of stakeholders in civil construction - Marques, Vânia de Lourdes; Filho, Cid Alledi; Pereira, Fernando Neves (Brazilian Journal of Operations & Production Management, 2018)
Highlights: Stakeholder management is an uncommon practice among construction companies in Brazil. There is little availability of appropriate models, guidelines and systematics. The creation of a stakeholder management model for civil construction is important in the current context. Goal: Contribute to fill the gap of empirical research that generate applicable models in the practices of stakeholder management in the civil construction sector. Design / Methodology / Approach: Systematic review of the literature was carried out involving the keywords of the research and, using the approach suggested by international standards guidelines, a management model for the management of stakeholders in the construction sector was constructed. Results: Two products resulted: a) Proposal of a conceptual framework for the management of stakeholders in civil construction, including a strategic and governance level and another with the ventures; b) Systematization of actions for stakeholder management, where the bibliographic content was distributed in stages based on the stakeholder management system proposed by the Standard AA1000SES. Limitations of the investigation: Difficulties in finding available literature on stakeholder management specifically in the civil construction sector, considering the strategic and governance level. Practical implications: Provides an innovative system for the strategic and tactical-operational management of stakeholders for the construction sector. Originality / Value: The research brings important contribution: in the academic area, for the few studies on the subject, especially in Brazil; for companies, it provides an innovative system with the following characteristics: ability to integrate stakeholder management practices between the corporate and project areas; ability to incorporate the experience and learning generated in both environments; applicable to any size of company.